Glycosylation of HIV-1 gp120 V3 Loop: Towards the Rational Design of a Synthetic Carbohydrate Vaccine - Sirois, Suzanne; Touaibia, Mohamed; Chou, Kuo-Chen; Roy, Rene (Current Medicinal Chemistry, 2007)
A wide variety of proteins can bind high-mannose oligosaccharides and are broadly neutralizing against HIV-1. However, success in eliciting broadly neutralizing antibodies against HIV-1 has been limited to date. The rational design of an HIV-1 vaccine is based on the information gained through the structural analysis of antibodies complexed with their epitopes. Of particular interest to this review are the binding of mannosides to human monoclonal antibody 2G12 recognizing Man9GlcNAc2 from HIV-1 gp120. It is widely recognized that T-cell-independent antigens carbohydrates are poorly immunogenic, and fail to induce memory. To increase the immunogenicity, carbohydrate antigens have to be coupled to a highly immunogenic carrier. The design of peptide carbohydrate mimotopes (mimetics of carbohydrate antigens) is one approach that is currently explored to elicit neutralizing antibodies. This work is concerned with existing structural data on Man9GlcNAc2 as the most promising epitope (or glycotope). Structural analysis of various torsion angles of Man9GlcNAc2 is explored. The focus is made primarily on the third variable region (V3 loop) of gp120 due to its crucial relevance for coreceptor usage, as a principal neutralizing determinant (PND), and for its conserved glycosylation sites N295, N302 and N332. Valuable structural information from glycosylation effects is taken into account for the development of a V3 loop rational structure-based vaccine strategy using N295 and N302 as potential conformational epitope.
Keywords: mannose binding protein